How do different functional crop groups perform in temperate silvoarable agroforestry systems? A Swiss case study - Christina denHond‐Vaccaro; Johan Six; Christian Schöb (Journal of Sustainable Agriculture and Environment, 2023)
Abstract Introduction Agroforestry systems provide a number of ecosystem services and are frequently considered as a promising diversification strategy for more sustainable and climate resilient primary production. However, most agroforestry field trials compare only one crop type with a control in open field. Additional comparisons between treatments that influence nutrient and water availability are often not looked at, nor are comparisons between crop species. Materials and Methods To deepen our understanding of the ecological processes underlying the potential benefits of agroforestry for food production, the present experimental study addresses three environmental factors (shade, fertilisation and irrigation) on three functionally different crop species (field bean, summer barley, summer rapeseed) and a C4‐grass (Echinochloa crus‐galli) in a Swiss agroforestry system. Crop performance (physiological traits, yield) between functional groups was analysed among treatment combinations of shade, fertilisation and irrigation. Physiological traits included measurements of chlorophyll content, stomatal conductance, specific leaf area and plant height. Results Summer barley and field bean showed significant yield declines when shaded (−44% and −38%, respectively), similar to summer rapeseed with a significant biomass decline (−35%). Shade significantly increased the occurrence of lodging in barley. Rapeseed in particular performed better when fertilised (+40% biomass). Conclusion The results allow to estimate the range of potential yield losses in the competitive zone near mature trees for functionally different crop groups. The findings serve as a decision‐support for species selection in temperate European agroforestry systems.